2009
DOI: 10.1042/bj20090086
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the interactions between endosomal adaptor protein APPL1 and the NuRD co-repressor complex

Abstract: Multifunctional adaptor protein APPL1 [adaptor protein containing PH (pleckstrin homology) domain, PTB (phosphotyrosine binding) domain and leucine zipper motif] belongs to a growing group of endocytic proteins which actively participate in various stages of signalling pathways. Owing to its interaction with the small GTPase Rab5, APPL1 localizes predominantly to a subpopulation of early endosomes but is also capable of nucleocytoplasmic shuttling. Among its various binding partners, APPL1 was reported to asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 56 publications
2
32
0
1
Order By: Relevance
“…It was previously documented that APPL1 interacts with the NuRD complex depending on the HDAC2 subunit. ( 15,27 ) In the present study, we observed APPL1 could colocalize with MTA2, HDAC1, and HDAC2 by confocal microscopy, and we also found the that three subunits could be pulled down by APPL1 with immunoprecipitation analysis. These results further confirmed Miaczynska’s theory that APPL1 interacted with the NuRD complex rather than a single component in the nucleus.…”
Section: Discussionsupporting
confidence: 74%
“…It was previously documented that APPL1 interacts with the NuRD complex depending on the HDAC2 subunit. ( 15,27 ) In the present study, we observed APPL1 could colocalize with MTA2, HDAC1, and HDAC2 by confocal microscopy, and we also found the that three subunits could be pulled down by APPL1 with immunoprecipitation analysis. These results further confirmed Miaczynska’s theory that APPL1 interacted with the NuRD complex rather than a single component in the nucleus.…”
Section: Discussionsupporting
confidence: 74%
“…Dab1 and Dab2, plasma membrane associated adaptors that are involved in endocytosis, were also shown to traffic to the nucleus [42,43], where Dab2 functions as a co-activator of TGFβ-dependent transcription [43]. On the other hand, APPL1 (adaptor protein, phosphotyrosine interaction, pleckstrin homology domain and leucine zipper containing 1), which associates with endosomal membranes and promotes membrane bending through its BAR (Bin/amphiphysin/Rvs) domain [44], was shown to interact in the nucleus with the NuRD (nucleosome remodelling and histone deacetylase) corepressor complex [45][46][47]. Thus endocytic proteins that shuttle to the nucleus may serve as co-activators or corepressors.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, these activities appear independent of endosomal localization of APPL2 and therefore could be mediated by its nuclear or cytoplasmic, but not endosomal, binding partners. Among others, APPL proteins interact with the nuclear proteins, such as nucleosome remodeling and histone deacetylase complex NuRD (Banach‐Orlowska et al., 2009; Miaczynska et al., 2004) or the multifunctional transcriptional regulator Reptin (Rashid et al., 2009). In the cytoplasm, APPL1 binds TRAF2 adapter protein which affects NF‐κB‐dependent transcription (Hupalowska et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the involvement of many endocytic proteins in the pathogenesis of cancer has been reported (Mosesson et al., 2008; Pyrzynska et al., 2009). Two homologous proteins APPL1 and APPL2 (adapter proteins containing pleckstrin homology domain, phosphotyrosine binding domain and leucine zipper motif) represent good examples of proteins actively participating in both endocytosis and cellular signaling (Banach‐Orlowska et al., 2009; Miaczynska et al., 2004; Rashid et al., 2009). In addition, some lines of evidence suggest a possible role of these proteins in cancer development and/or progression.…”
Section: Introductionmentioning
confidence: 99%